In the name of - Palpa, Daniel (My University, 2025)
This thesis project explores the intersections of contemporary art and societal tensions through a large-scale, three-tiered altar installation titled In The Name Of. Drawing from religious symbolism and contemporary socio-political discourse, the work challenges notions of power, identity, gender, and digital influence. By reconstructing the traditional Catholic altar structure, the installations serves as both a visual and conceptual framework, that interrogates modern societal issues, and the evolving discourse on representation and ideology. By merging personal narrative with broader societal critique, In The Name Of act as a vessel for collective introspection. It urges audiences to confront the pervasive influence of media, the commodification of cultural and religious symbols, and the ongoing struggle between representation and reality.
Keywords: taiteilijat; nykytaide; tilataide; taide; kuvataide; valta; ikonografia; installaatiot; fi=kuvanveisto|sv=skulptur|en=Sculpture|